The Response, Outcome and Toxicity of Aggressive Palliative Thoracic Radiotherapy for Metastatic Non-Small Cell Lung Cancer Patients with Controlled Extrathoracic Diseases. - Yun Chiang; James Chih-Hsin Yang; Feng-Ming Hsu; Yu-Hsuan Chen; Jin-Yuan Shih; Zhong-Zhe Lin; Keng-Hsueh Lan; Ann-Lii Cheng; Sung-Hsin Kuo (PLoS ONE, 2015)
BACKGROUND AND PURPOSE:For metastatic non-small cell lung cancer (NSCLC) patients with controlled extrathoracic disease after systemic treatment, stable or progressive primary lung lesions may cause respiratory symptoms and increase comorbidities. In the present study, we sought to investigate whether aggressive palliative thoracic radiotherapy (RT) can enhance local control and improve the survival for this subgroup of patients. MATERIALS AND METHODS:Between March 2006 and December 2014, 56 patients with metastatic NSCLC who had responsive or stable extrathoracic diseases after chemotherapy and/or molecular targets, and received thoracic RT for stable and progressive primary lung lesions were included. RT with a median dose of 55 Gy (range, 40-62 Gy) was administered in 1.8-2.5 Gy fractions to primary lung tumor and regional mediastinal lymph nodes using modern RT technique. Overall survival (OS) from diagnosis, and locoregional progression-free survival (LRPFS), and survival calculated from radiotherapy (OS-RT) were estimated using the Kaplan-Meier method. RESULTS:There were 37 men and 19 women with a median age of 60 years at diagnosis. The median interval from the diagnosis of metastatic disease to thoracic RT was 8 months. Following thoracic RT, 26 patients (46%) achieved complete or partial response (overall response rate, ORR). Patients with squamous cell carcinoma or poorly-differentiated carcinoma had a higher ORR than those with adenocarcinoma (63% vs. 34%, P = 0.034). EGFR mutations was closely associated with a better ORR (45% vs. 29%, P = 0.284). At a median follow-up time of 44 months, the median OS, LRPFS after RT, and OS-RT were 50 months, 15 months, and 18 months. CONCLUSION:Radical palliative throractic RT is safe and might be beneficial for primary lung lesions of metastatic NSCLC patients with controlled extrathoracic diseases.